Influence of plant soil mixtures on plant vegetation - Anatoly E. Unitsky; Nikifor S. Zyl; Mikhail I. Tsyrlin; Aleksandr M. Pavliuchenko; Mikhail M. Parfenchik (RUDN Journal of Agronomy and Animal Industries)
The study was focused on investigating the effect of composition of light soil on vegetation of lettuce plants. Nowadays, reducing the density of plant substrates is becoming an important component for obtaining quality products. This soil property is not so essential for growing crops in the field. But using a specially prepared substrate for cultivating plants in various types of multi-tier greenhouses, eco-villages with roof gardens, and private bio-domes, it is important. This feature is due to the following: the higher the density of the applied substrate, the greater the strength that needs to be considered when designing the supporting structure of objects and the more materials will be required. This means that the cost of construction will be higher. Therefore, the issue of creating a light, but at the same time fertile substrate for plants, which will allow obtaining environmentally friendly plant products and at the same time will have a low density relative to natural soil, is currently being actively studied. The light soil tested was perlite with addition of biohumus. For foliar feeding, uTerra organic complex was used. It was determined that the best variant for light soil was perlite with addition of 10% (by volume) of uTerra crumbly biohumus. Thus, the article discusses current issues of structure of fertile soil, possible options for composition of a lightweight substrate based on mineral components (perlite, expanded clay) and biohumus suitable for growth and development of plants. In addition, the experiment concerning the study of the influence of light soil on plant crops was described, conclusions are drawn and its results were substantiated. The final part summarizes the work done and outlines its future prospects.